Analysis Of Factors Affecting Vannamei Shrimp Production at PT Bengkulu Sukses Lestari Aquaculture (PT. BSLA) - Ali Fahmi Syahputra; Rhochmad Wahyu Illahi; Yeni Sari Wulandari; Amalia Febryane Adhani Mazaya; Elfa Fitriana (Grouper, 2026)
Vannamei shrimp has several advantages for aquaculture, including a strong feeding response, high appetite, relatively high resistance to poor environmental conditions, rapid growth, and high survival rate. In the current competitive business environment, aquaculture enterprises are required to optimize production processes to improve productivity and maintain competitiveness. This study aimed to identify the production factors affecting vannamei shrimp production at PT Bengkulu Sukses Lestari Aquaculture (PT BSLA), both partially and simultaneously. The study was conducted at a single pond site owned by PT BSLA using a quantitative descriptive method. Four independent variables were analyzed, namely land area (X1), fry (X2), feed (X3), and labor (X4), while production was used as the dependent variable. Data were analyzed using multiple linear regression with SPSS. The results showed that land area and labor had a significant partial effect on vannamei shrimp production, while fry and feed did not show a significant partial effect. Simultaneously, land area, fry, feed, and labor significantly affected vannamei shrimp production. These findings imply that optimizing land utilization and labor management is essential to improve the productivity and sustainability of vannamei shrimp farming at the company level.